Service recovery strategy and customer satisfaction in higher education - Yeop Yunus, Nek Kamal (2004)
This study reports customer recovery satisfaction in educational settings. Most of previous research has been conducted in banks, restaurants and hotels but none of those were from educational context. There has been keen interest in customer recovery satisfaction recently. During the service encounter, customers witnessed the dyadic interactions and experienced the moments of truth. The parties involved are customers, service providers, the physical environment of the service organization and the failure atonement. Despite the best efforts made by the service firms, service failures are inevitable. When service fails, the dissatisfied customers defect to competitors thereby firms loses business, suffer bad word of mouth and grudges. Service firms should recover. It was hypothesized that communications, explanation, feedback, empowerment, tangible, speed and atonement would influence customer recovery satisfaction. It was also hypothesized that organizational climate would moderate the relationship. Data for the study was collected from randomly sampled 103 post-graduate students in a public university in Malaysia using structured questionnaire. Analysis showed that tangible, communication, feedback, and atonement, have positive significant relationship with customer retention as they were enhanced by the organizational climate, as much as, 14.7%, 14.5%, 15% and 15.7% respectively. It was also found that these four variables predicted to contribute 10.7%, to the customer retention rate. Recommendations for further research were also discussed.